Synthesis of Bimetallic Catalysts on the Basis of Y Type Zeolite - Ahmed, Kanaan R. (Science Journal of University of Zakho, 2020)
In this work, it is shown that based on powder zeolite type Y, mono metallic and bimetallic catalysts have been developed that are promising for petroleum chemistry processes. The method is based on the preparing hydrogen form of Y zeolite by ion exchange with a solution of ammonium nitrate at a starting concentration of 70 g.l-1 and nickel nitrate solution which provides Ni cations. Then after preparation of bimetallic catalysts by impregnating second metal by incipient wetness. All samples and catalysts were characterized using X-ray diffraction (XRD) analysis techniques, adsorption methods, and elemental analysis. The research results showed that in order to reach the degree of exchange of Na+ for H+ cations  no less than 0.73, it is necessary to carry out four exchanges of Na+ by NH4+ and three intermediate thermal treatments at 540 °C for 3 to 4 hours in air atmosphere.
Keywords: Bimetallic Catalysts; Zeolites; Petroleum Chemistry; Solid Acid Catalysts; Industrial Catalysts